Quantifying Public E-Participation through Social Media in Government Decision Making - Hapini, Awang; Isyaku Uba, Haruna; Maslinda, Mohd Nadzir; Osman, Ghazali; Nur Suhaili, Mansor; Mohamad Fadli, Zolkipli (INTI International University, 2025)
The evolution of Information and Communication Technology (ICT) has enabled governments to implement online services, enhancing citizen participation in decision-making. Within e-government initiatives, e-participation plays a critical role in shaping public policies. However, a significant gap remains—the lack of a reliable instrument to measure and assess public e-participation through social media in government decision-making. Existing studies have explored e-participation factors but have not provided a validated tool for systematically evaluating this engagement. This study aims to bridge this gap by developing a reliable instrument based on a pilot study. A structured survey instrument was designed and validated through expert review and a pilot study involving 35 respondents. Statistical validation confirmed high construct reliability (Cronbach’s alpha > 0.6), ensuring the instrument's suitability for further research and practical application. The findings contribute to both academic literature and policymaking by providing a validated framework for assessing and enhancing citizen engagement in e-government.